2016
DOI: 10.1155/2016/3057384
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Oxidation Sensitivity of Red Blood Cells and Carbonic Anhydrase Activity in Stored Human Blood: Effect of Certain Phenolic Compounds

Abstract: It has been reported that many modifications occur with the increase of oxidative stress during storage in erythrocytes. In order to delay these negative changes, we evaluated whether the addition of substances likely to protect antioxidant capacity in stored blood would be useful. Therefore, we investigated the effects of resveratrol, tannic acid, and caffeic acid in lipid peroxidation and antioxidant capacity of erythrocytes in stored blood. Donated blood was taken into four CPD containing blood bags. One ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…Because of a possible increase in 8-OHDG levels in stored blood can cause gene mutations and false protein coding after blood transfusion, it is important to prevent injury in the DNA bases. Increasing oxidative stress and decreasing antioxidant capacity due to storage time (3,9,15,17,26), especially OH . radicals, can lead to DNA oxidation by damaging nuclear proteins and DNA (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of a possible increase in 8-OHDG levels in stored blood can cause gene mutations and false protein coding after blood transfusion, it is important to prevent injury in the DNA bases. Increasing oxidative stress and decreasing antioxidant capacity due to storage time (3,9,15,17,26), especially OH . radicals, can lead to DNA oxidation by damaging nuclear proteins and DNA (9).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 60 µg/mL resveratrol and 60 µg/mL serotonin was added to the second and third group, respectively. For blood storage time and measurement intervals, time intervals specified by previous studies were selected (15,17,26). For this purpose, MDA and oxidized CoQ10 were measured in the samples taken at the beginning, 7, 14, 21 and 28 days in all groups.…”
Section: Establishment Of Groups and Measurement Intervalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The susceptibility to in vitro oxidation of erythrocytes was performed according to the method used by Huyut et al . For this purpose, a suspension of erythrocyte with azide buffer was prepared and MDA level was measured spectrophotometrically at 532 nm with thiobarbituric acid (TBA) reagent (baseline).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…These criterias; during the storage period rate of hemolysis in erythrocytes should not exceed 1% and after the transfusion at least 75% of RBCs should stay alive in the first 24 hours (3). In many clinical situation, blood transfusion is necessary, such as deep anemia, acute blood loss and some surgeries (4,5). Several studies indicated that while the stored blood maintained at optimum conditions, some adverse change occurs called as "storage lesion" time-dependently.…”
Section: Introductionmentioning
confidence: 99%